A framework for cost assessment of qms for building contractors based on biological immune system - Keyvanfar, Ali (2009)
Quality as a traditional objective in construction industry that is lacking of quantitative assessment approach has been planned and evaluated in qualitative manner. Study in order to develop a feasible quantitative QMS (Quality Management System) assessment framework, has been considered Cost of Quality as a quantitative measurement to evaluate the success of quality program in a self-improvement organization. Therefore, in this study, elements of cost of quality in several approaches have been reviewed. Besides, principles of several QMS tools and techniques: Taguchi methods, process of Failure Mode and Effect Design (FMEA), Benchmarking techniques, Shainin, Demings 14 point for Plan for TQM, Six-Sigma and finally Kaizen management philosophy are reviewed. Furthermore, objectives of Biological Immune System (BIS) to capture the success factors of an intelligent system have been reviewed. Through this study, proposed intelligent based framework model and its tools and descriptions have been developed. For evaluating finding objectives, each finding has been discussed with relevant field of research experts. Finally feasible validations were made by questionnaires on 5 industrial experts.